Lithium Lactate Modified Polyolefin Separators for High-Performance Lithium Metal Batteries - Wang, Lulu (Langmuir : the ACS journal of surfaces and colloids, 2025)
As the fast-paced evolution of high energy density rechargeable batteries continues, the lower lithium ion (Li+) mobility of polyolefin separators has become a major bottleneck in the adoption of lithium metal electrodes. With undesired Li+-anion solvated structures in the electrolyte, previous separator modification strategies are generally confronted with the dilemma of concurrently enhancing the Li+ transference number and reducing the anion transference number, as well as overall conductivity. Here, a strategy are reported to prepare high-performance separators with polyolefin separators coated by lactic acid lithium with the assistance of dopamine hydrochloride and triethanolamine, which can achieve a stable LMB operation at 1 C for 600 cycles with a capacity retention of 92%, substantially outperforming pristine PP separator. The ultrathin polar modification layer on the surface of the PP separator renders optimal electrolyte wettability and notable electrolyte uptake. The electrostatically repellent nature of the negatively charged -COO- moieties on the ion permeable layers can effectively increase the Li+ transference number without sacrificing the overall ion conductivity. The ionic conductivity of the DL2-PP separator reaches 1.2 mS cm-1, and the lithium-ion mobility is 0.68, enabling a rapid, selective and uniform Li+ flux through the separator. DFT calculations are utilized to analyze the underlying mechanism. Such features can facilitate uniform nucleation/deposition of Li and mitigate Li dendrite growth, leading to enhanced battery durability and safety